Carbamate as an accelerating group in intermolecular Pauson-Khand reaction. Issue 24 (11th June 2020) - Asano, Shota; Itto-Nakama, Kaori; Arimoto, Hirokazu
Graphical abstract: Highlights: Examples of intermolecular Pauson-Khand reaction (PKR) have been limited to reactive alkene substrates. Carbamate in alkene substrates was demonstrated to facilitate intermolecular PKRs. Arylalkynes are the suitable substrates of this reaction. Abstract: The Pauson-Khand reaction (PKR) is a powerful means for the construction of cyclopentenones. However, its applications have been limited to the intramolecular version of this reaction because poor yield and regioselectivity are often the major problems in intermolecular PKR. Here we describe that a carbamate moiety in alkene substrate accelerates this intermolecular PKR. The reaction of N- 4-dimethylaminophenyl O- allyl carbamate with alkyne-cobalt complex gave cyclopentenones in high yield (up to 90%) and regioselectivity (>9:1).